A REVIEW ON EXTRACTION OF LIPID FROM MICROALGAE USING MICROWAVE-ASSISTED EXTRACTION - Hwang T.Y.; Kin C.M.; Shing W.L.; Subramaniam G. (Malaysian Society of Analytical Sciences, 2024)
Microalgae are regarded as suitable feedstock for biofuel due to their high growth rate and substantial lipid content Furthermore, the physiological functions of microalgal lipids contribute to their effectiveness as bioactive compounds with economic value particularly in pharmaceutical and health supplement industries. Extracting the stored lipid from microalgae is a major challenge for industrial applications as their tough cell wall is difficult to break down. Therefore, extraction solvents and cell disruption techniques are key procedures for high lipid extraction and recovery. Traditional methods used for cell disruption and extraction are effective but time consuming and could be detrimental to the environment. Hence, different innovative cell disruption techniques such as microwave-assisted extraction are developed to overcome these issues. This paper is a review of traditional and microwave-assisted extraction methods that are used for lipid extraction from microalgae biomass. The advantages, challenges and future trends of microwave-assisted extraction are also discussed. 2023, Malaysian Society of Analytical Sciences. All rights reserved.